TAX FRAUD AS THE MOST SEVERE FORM OF TAX EVASION: REVIEW OF LEGISLATION AND PRACTICE IN SERBIA - Dimić, Suzana (COLLECTION OF PAPERS, FACULTY OF LAW NIŠ, 2021)
Bearing in mind that taxation reduces disposable income, it is understandable that taxpayers' resistance to tax compliance is understandable. That is why in modern financial theory and practice, particular attention is paid to the popularization of taxes, with reference to the purpose of taxation. Taxes are acceptable to taxpayers insofar as they are funded by public goods of which they are beneficiaries.Unlike other criminal offenses, in which the detrimental effect may be directly visible, the immediate detrimental effect in tax offenses is not transparent. Therein lies one of the significant problems - the psychological effect that tax acts have little or even negligible social danger, which cannot be accepted as true. On the contrary, tax offenses represent socially very dangerous behaviors because they threaten the fiscal interests of the state. Only timely payment of taxes and other duties ensures continuity in financing public needs, and thus regular functioning of the state. With tax evasion, and even tax fraud as its most difficult form, the state remains deprived of the amount of revenue that would have been collected had all taxpayers obeyed the tax liability.Particular attention is given in this paper to the normative framework in Serbia, as well as to the basic issues that arise in practice. The reason for this is the long-standing mild criminal policy of the courts in Serbia, with numerous problems in processing tax evasion (from difficulties in conducting a financial investigation to requiring a basic level of knowledge of judges in this field). The question arises whether, in view of the harmful consequences for the fiscal system of the state, the tax evasion in Serbia has been criminilaised. It seems that the latest changes to the law, which has increased the census (the amount of evasion tax) for this crime, will mean "moving away" from an adequate condemnation of such behavior as socially unacceptable. This can only adversely affect the already low level of tax morale in Serbia.
Keywords: taxpayers; tax evasion; tax fraud; fiscal offenses; tax and contribution avoidance